Implant-related artifacts around metallic and bio-integrative screws: a CT scan 3D Hounsfield unit assessment - VandeLune, Christian; Tazegul , Tutku; J Ahrenholz, Samuel; Iehl, Caleb; Vivtcharenko, Victoria; Schmidt, Eli; N Dibbern, Kevin; Lee, Hee Young; Lalevee, Matthieu; Barbachan Mansur, Nacime Salomão; et al. (Journal of the Foot & Ankle, 2021)
Objective: To assess the degree of implant-related artifacts (IRA) around metallic and bio-integrative (BI) cannulated screws using Hounsfield units (HU) on computed tomography (CT). Our hypothesis was that BI implants would demonstrate significantly decreased IRA around the inserted screws. Methods: In this cadaveric CT imaging study, we used 2 below-knee specimens. Medial displacement calcaneal osteotomy was performed, and the specimens were fixed with either metallic or BI screws. HU values were measured over 4 different lines that crossed the osteotomy position. Results: The mean HU value was decreased in the BI implants compared to the metallic ones in 3 different positions: near the screw, directly over the screw, and inside the screw cannula. At the line placed 1 cm dorsal to the screw, the HU value for the metallic screw was lower than that for the BI screw. Conclusions: We found metallic implants to demonstrate significantly increased HU values in regions close to the implant and significantly decreased values 1 cm away from the implant, when compared to the BI screw. The decreased HU values 1 cm away from the implant could be due to a shielding effect of the surrounding bone, hindering the assessment of union and healing. BI implants represent an alternative to decrease these IRA effects. Level of Evidence III; Case-Control Study.